(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
The fall of the Berlin Wall and the implosion of the Soviet Union created an effect comparable to culture shock in worldwide public opinion. These events were interpreted as an epochal change: a political revolution that opened a new era of human history. In the 1990s, various theories of global society were proposed. These theories also open news paths for social and political analysis. Viewed with unprejudiced eyes, history does not seem to have reached its fulfillment and turns out to be more complex than a bipolar structure (the democratic and capitalistic Western World vs. the anti-democratic and totalitarian Communist world) or tripolar structure (the First, Second and Third worlds) of the “Cold War” period. By discussing some of these interpretations through the intertwining of the concepts of “civilization” and “globalization” and through a comparison with non-Western or non-Modern frameworks of civilization, this essay underlines that every civilization has its own idea and its own project for a global society: comparative analysis shows the possibility of dialogue and, at the same time, the risks of conflict.